2004
DOI: 10.1128/jcm.42.10.4512-4518.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Real-Time PCR Assay for Detection of Helicobacter pylori Infection and Simultaneous Clarithromycin Susceptibility Testing of Stool and Biopsy Specimens

Abstract: A biprobe real-time PCR protocol, followed by hybridization melting point analysis, to detect point mutations in the 23S rRNA gene of Helicobacter pylori associated with clarithromycin resistance was established and evaluated in a clinical study. Of 92 patients who underwent endoscopy, 45 were found to be H. pylori infected and invariably were also culture positive. Of the 45 isolates, 11 were shown to be resistant to clarithromycin by E-test. With respect to the detection of H. pylori infection, PCR showed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 23 publications
4
139
0
6
Order By: Relevance
“…Agar dilution is the recommended test of choice although the Etest has proven to provide clinically reliable except with metronidazole where it tends to overestimate the presence of resistance and must be confirmed by agar dilution methods. Molecular methods of detection of specific changes in the organisms' genome are alternative approaches to detection of resistance and in theory allow a more rapid detection of resistance as well as detection of resistance using stool or biopsy specimens 23,24 .…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…Agar dilution is the recommended test of choice although the Etest has proven to provide clinically reliable except with metronidazole where it tends to overestimate the presence of resistance and must be confirmed by agar dilution methods. Molecular methods of detection of specific changes in the organisms' genome are alternative approaches to detection of resistance and in theory allow a more rapid detection of resistance as well as detection of resistance using stool or biopsy specimens 23,24 .…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…The lowest H. pylori DNA concentration detected was 10 fg, equivalent to 5 bacterial cells (Mikula et al, 2003;Schabereiter-Gurtner et al, 2004). In a range between 10 to 10 6 fg correlation coefficients, obtained by lin- ear regression analysis from all independent experiments, were higher than R 2 = 0.99, indicating highly efficient and reproducible reactions.…”
mentioning
confidence: 98%
“…Recently, five studies have shown that RT-PCR can be used to detect and quantify H. pylori DNA directly from gastric biopsy samples (He et al, 2002;Kobayashi et al, 2002;Lascols et al, 2003;Mikula et al, 2003;Schabereiter-Gurtner et al, 2004). Additionally, RT-PCR has been validated for the quantitative analysis of the low level of bacterial infection in immunized and experimentally infected mice, suggesting that this methodology may also be useful for the evaluation of new anti-H. pylori drugs and vaccines (Mikula et al, 2003).…”
mentioning
confidence: 99%
“…Culture is currently accepted gold standard for the diagnosis of gastric H. pylori (Makristathis et al, 2004). This method achieve 80-90% sensitivity and 90-100% specificity rates (Hep 2003).…”
Section: Methods Of H Pylori Detection In the Oral Cavity And Pharynxmentioning
confidence: 99%